2009
DOI: 10.1371/journal.pone.0007964
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1-Related Coactivator Modulates Mitochondrial-Nuclear Crosstalk through Endogenous Nitric Oxide in a Cellular Model of Oncocytic Thyroid Tumours

Abstract: BackgroundThe PGC-1 related coactivator (PRC), which shares structural and functional features with PGC-1α, is believed to regulate several metabolic pathways as well as mitochondrial biogenesis. Its involvement in the early programming of cell proliferation suggests the existence of finely regulated crosstalk between mitochondrial functions and the cell cycle status.Methodology/Principal FindingsPRC-regulated pathways were explored in a cell-line model derived from mitochondrial-rich tumours with an essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 54 publications
4
32
0
1
Order By: Relevance
“…The observed early increase in PPRC1 expression upon initiation of cell growth paralleled nicely the rapid induction of PPRC1 expression observed upon the initiation of growth in cultured human and mouse cells (Vercauteren et al, 2006(Vercauteren et al, , 2009Raharijaona et al, 2009). Nanog and Gata6 are important transcription factors in mouse embryonic differentiation.…”
Section: Developmental Dynamicssupporting
confidence: 61%
See 2 more Smart Citations
“…The observed early increase in PPRC1 expression upon initiation of cell growth paralleled nicely the rapid induction of PPRC1 expression observed upon the initiation of growth in cultured human and mouse cells (Vercauteren et al, 2006(Vercauteren et al, , 2009Raharijaona et al, 2009). Nanog and Gata6 are important transcription factors in mouse embryonic differentiation.…”
Section: Developmental Dynamicssupporting
confidence: 61%
“…In contrast to PGC-1a and PGC-1b, which show tissue-specific expression and distinct physiological roles in some oxidative tissues (Puigserver et al, 1998;Wu et al, 1999;Lin et al, 2002;Kamei et al, 2003;St-Pierre et al, 2003), PPRC1 appears to have a more ubiquitous expression pattern in adult and embryonic tissues (Andersson and Scarpulla, 2001;Vercauteren et al, 2006Vercauteren et al, , 2008Vercauteren et al, , 2009Raharijaona et al, 2009). The ubiquitous expression pattern suggests a housekeeping role of PPRC1, which may be more universal and important for cell survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our findings have revealed that treatment of osteosarcoma cells with 2-ME at physiological concentrations resulted in significantly lower nuclear NO levels than treatment with 2-ME at pharmacological concentrations (18). Differential effects depending on NO exposure time and concentration have previously been reported (17). In a long-term effect, a NOdependent pathway has been shown to control mitochondrial biogenesis through up-regulating PGC-1α, the crucial regulator of mitochondrial biogenesis (15)(16)(17).…”
Section: Figure 8 Root Mean Square Deviation (Rmsd) Of Two 2-methoxymentioning
confidence: 52%
“…Clinical analysis of human invasive breast cancers has revealed a strong correlation between PGC-1α expression in invasive cancer cells and the formation of distant metastases, while PGC-1α silencing has suspended their invasive potential and attenuated metastasis (11)(12)(13). Importantly, mitochondrial respiration and mitochondrial biogenesis remain under the strict control of nitric oxide (NO) (14)(15)(16)(17). Furthermore, as indicated by Aquilano and coauthors, the nuclear recruitment of neuronal nitric oxide synthase (nNOS) and generation of NO in the nucleus are mandatory for the induction of the mitochondrial biogenesis pathway (14).…”
mentioning
confidence: 99%